Object Relations Theory, Mothering, and Religion: Toward a Feminist Psychology of Religion - Jonte-Pace, Diane (Horizons, 1987)
Although psychoanalytic object relations theory has been acclaimed for its ability to revitalize the psychological understanding of religion, the implicit sensitivity of object relations theory to feminist concerns has not been recognized. This paper suggests that object relations theory shares with feminist thought three central foci: relationality, mature dependency, and a revaluing of the mother-infant relationship. Through this coincidence of concern object relations theory can move toward a feminist psychology of religion which avoids not only Freud's reductionism toward religion, but also his patricentrism. The psychological antecedents of religious experience, ritual, and the image of God are examined from the object relational perspective, and are located in the maternal-infant matrix. It is suggested that this linkage of culture and mother offers a radical challenge to the psychoanalytic perspective.